Penyuluhan Kesehatan dan Kebugaran Jasmani Al-Qodir - Ginanjar Nugraheningsih; Ayub Tatya Admaja; Heri Nuryanta; M.Taufik Novianto (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
PPM is in partnership with MTs and MA Al Qodir which is located in the Salafiyah Al Qodir Islamic Boarding School, Wukirsari Hamlet, Cangkringan District, Sleman. There are 84 students of MTs Al Qodir and 65 students of MA Al Qodir. The total participants are 149 students. The program carried out, namely Al-Qodir health and fitness education is relevant to the current conditions facing Covid-19. Through this activity, students are expected to have: (1) awareness of better health and physical fitness, (2) new motivation to be more diligent in maintaining personal hygiene and physical fitness in the madrasa environment, (3) routine agenda of cleaning yourself and the environment as outlined in the “Healthy Friday” activity (4) has a good immune system in a covid-19 situation. The methods used are lectures, demonstrations and observations of students' physical health and fitness. The results showed an increase in awareness of the culture of healthy living and maintaining physical fitness as well as the "Healthy Friday" agenda. The importance of understanding so that it can apply to oneself and the environment because in addition to being a student at a madrasah they are also a santri of a boarding school who is far from their parents. They are required to be independent, not dependent on other people and to be smart about maintaining their health and physical fitness, especially during the Covid-19 period. It was concluded that this activity was very good to do and it was recommended that the program be sustainable